Long-Range Control of Class Switch Recombination by Transcriptional Regulatory Elements - Dauba, Audrey; Khamlichi, Ahmed Amine (Frontiers in Immunology, 2021)
Immunoglobulin class switch recombination (CSR) plays a crucial role in adaptive immune responses through a change of the effector functions of antibodies, and is triggered by T cell-dependent as well as T cell-independent antigens. Signals generated following encounter with each type of antigen direct CSR to different isotypes. At the genomic level, CSR occurs between highly repetitive switch sequences located upstream of the constant gene exons of the immunoglobulin heavy chain locus. Transcription of switch sequences is mandatory for CSR and is induced in a stimulation-dependent manner. Switch transcription takes place within dynamic chromatin domains and is regulated by long-range regulatory elements which promote alignment of partner switch regions in CSR centers. Here, we review recent work and models that account for the functions of long-range transcriptional regulatory elements and the chromatin-based mechanisms involved in the control of CSR.